Improving pervasive application behaviour with other users' information - Spence, Michael (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
The behavior of a pervasive application is much improved with access to accurate, relevant information describing the situation of the application's user. Unfortunately, sensor failure, sensor drift, and device mobility mean that the primary sources of informationare not guaranteed to always be available or applicable. A promising alternative source is the information describing other users. The use of information from other users has the potential to allow a pervasive application to utilize the knowledge, experience, reasoning methods, and sensors of other users' devices in the environment. Despite its potential benefits, there are two reasons why a convincing case has, to date, not been presented for the utilization of other users' information to improve accuracy in pervasive applications.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.